If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-2 + -9x) = 0 (-2 * -1 + -9x * -1) = 0 (2 + 9x) = 0 Solving 2 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 9x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 9x = 0 + -2 9x = 0 + -2 Combine like terms: 0 + -2 = -2 9x = -2 Divide each side by '9'. x = -0.2222222222 Simplifying x = -0.2222222222
| 21-18x=-3*(6x-7) | | y=70+0.5x | | -35-7r=-7(r+5) | | x=70+-0.5y | | 2*e^2x-4=14 | | 0.3+1.38=0.24x+1.2 | | 19x+17x+27=180 | | 70-6N= | | -15-k=k+1 | | Ln^2(X)+5ln(X)=14 | | 3w^2-5w-78=0 | | (5+w)(5w-9)=0 | | 35+11x=90 | | 3x+5+7x-7=180 | | 5/8+1/6z=5/12+2 | | .25z(3x-4)-.5x=2.75 | | y/9+89=96 | | x+10+2x+5+90=180 | | 15a-6ab= | | 8x^3+12x^2-4x=6 | | 6-7x+2=x+36 | | X^3x-4=0 | | 15+5k=1+7k | | 2=8a | | 10x+32=135 | | -4[x-5]=12 | | F(x)=x^2+8x-4 | | 2b=-22-9b | | 4x+8=45 | | 2x-3(4x+1)=9 | | 11x-35=24x-31 | | [x+3]=15 |